Securing the Maritime Domain: U.S. and New Zealand in a Bordered Pacific - Nicklin G (Centre for Defence and Security Studies, Massey University)
Maritime security in the Pacific differs according to whose security is under threat and in what geographical location. Like the fluidity of the ocean, maritime security is dynamic involving multiple interests. But the Pacific is also a very bordered space. Drawing on a December 2019 study tour of US defence facilities in Hawai’i, this article addresses the question “How are United States (US) and New Zealand maritime security interests bordered in the Pacific and what are the implications?” First, the article situates maritime security within state territoriality and defence of borders. It then examines the Pacific Ocean as a bordered space, and sketches US and New Zealand interests within it, including differentiating Indo-Pacific from Pacific. Next, each country’s means of securing their maritime domains in the Pacific is explicated, the arenas of cooperation and gaps in knowledge worth researching further. It concludes by discussing US-NZ maritime cooperation within the framing of a Pacific maritime borderscape. One potential borderscape is the Polynesian Triangle. This article argues that defining a specifically bordered theatre of cooperation such as the Polynesian Triangle, driven by Pacific Island needs, is required to provide balance and visibility to non-military maritime security matters. Such a theatre of cooperation warrants further research.
Keywords: borderscape; Indo-Pacific; Maritime security; New Zealand; Pacific; United States